Rab27a Is an Essential Component of Melanosome Receptor for Myosin Va - Wu, Xufeng (The American Society for Cell Biology, 2002)
Melanocytes that lack the GTPase Rab27a (ashen) are disabled in myosin Va-dependent melanosome capture because the association of the myosin with the melanosome surface depends on the presence of this resident melanosomal membrane protein. One interpretation of these observations is that Rab27a functions wholly or in part as the melanosome receptor for myosin Va (Myo5a). Herein, we show that the ability of the myosin Va tail domain to localize to the melanosome and generate a myosin Va null (dilute) phenotype in wild-type melanocytes is absolutely dependent on the presence of exon F, one of two alternatively spliced exons present in the tail of the melanocyte-spliced isoform of myosin Va but not the brain-spliced isoform. Exon D, the other melanocyte-specific tail exon, is not required. Similarly, the ability of full-length myosin Va to colocalize with melanosomes and to rescue their distribution in dilute melanocytes requires exon F but not exon D. These results predict that an interaction between myosin Va and Rab27a should be exon F dependent. Consistent with this, Rab27a present in detergent lysates of melanocytes binds to beads coated with purified, full-length melanocyte myosin Va and melanocyte myosin Va lacking exon D, but not to beads coated with melanocyte myosin Va lacking exon F or brain myosin Va. Moreover, the preparation of melanocyte lysates in the presence of GDP rather than guanosine-5′-O-(3-thio)triphosphate reduces the amount of Rab27a bound to melanocyte myosin Va-coated beads by approximately fourfold. Finally, pure Rab27a does not bind to myosin Va-coated beads, suggesting that these two proteins interact indirectly. Together, these results argue that Rab27a is an essential component of a protein complex that serves as the melanosome receptor for myosin Va, suggest that this complex contains at least one additional protein capable of bridging the indirect interaction between Rab27a and myosin Va, and imply that the recruitment of myosin Va to the melanosome surface in vivo should be regulated by factors controlling the nucleotide state of Rab27a.